The Relationship Between Peer Support and the Incidence and Dimensions of Burnout Among Medical Students - Naf'an, Nabila Utiya; Prathita, Yana Aurora; Lestari , Yani Dwi (Jurnal Medis Islam Internasional, 2025)
Introduction: Burnout is a psychological condition characterized by chronic stress that persists over a long period as a response to ongoing stressors. Burnout can lead to decreased academic performance, increased risk of dropout, and even suicide. Peer support may enhance self-confidence, reduce social pressure, and provide emotional stability, ultimately helping reduce the risk of burnout. Objective: This study examines the relationship between peer support and burnout among medical students at Sultan Ageng Tirtayasa University (Untirta). Methods: The research design employed was a cross-sectional design, utilizing the simple random sampling technique for data collection. The subjects were preclinical medical students from the 2021, 2022, 2023, and 2024 cohorts. Sampling was conducted using a simple random sampling technique. Data on peer support were collected using the Social Provision Scale (SPS), while burnout data were obtained through the Maslach Burnout Inventory–Student Survey (MBI-SS). The data were analyzed using univariate and bivariate analyses. Results: The results showed that the prevalence of burnout among students was 14.6%. Based on the dimensions of burnout, the majority of students reported high levels of exhaustion (58.4%), moderate levels of cynicism (47.2%), and low efficacy (100%). Regarding peer support, 96.6% of students reported high levels of peer support. Fisher's exact test yielded a p-value of 0.381. Conclusions: This study concludes that there is no significant relationship between peer support and burnout among medical students at the University